Coupling of water and ion fluxes in a K+-selective channel of sarcoplasmic reticulum. - Miller, C (1982)
Streaming potentials arising across a K+-selective channel from fragmented sarcoplasmic reticulum were measured by incorporating the channel into planar bilayer membranes and imposing osmotic gradients across the membranes by addition of sorbitol or urea to only one side. Single-channel zero-current potentials were determined, and dilution artifacts were corrected for by addition of valinomycin to the bilayer. The streaming potentials were found to be unusually small, 1.1 mV per osmolal. The potentials were linearly related to the osmotic gradient across the bilayer, and were identical for sorbitol and urea. The results imply that the channel cannot be envisioned as a long tube, like gramicidin, but rather as a short constriction of less than 10 A in length opening out into wider mouths on either side of the membrane.